High-temperature speckle preparation method suitable for silicon carbide ceramic-based composite material
The suspension is prepared by mixing high-melting point resistant hafnium oxide (HfO2) with dilute nitric acid and deionized water, and spraying it onto the surface of SiC ceramic-based composite material. Combined with the natural oxidation process of SiC ceramic-based composite material, the speckle is pinned on the surface of the sample, solving the problem that the speckle is prone to oxidation, deformation and fall off in high-temperature aerobic environment, and achieving the accuracy and reliability of high-temperature strain measurement.
Patent Information
- Application Number
- CN202510523879.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2025-06-20
AI Technical Summary
In the prior art, the speckle used by SiC ceramic matrix composites in high-temperature aerobic environments has problems such as oxidation, deformation, and easy shedding, and it is impossible to effectively conduct strain measurement and damage monitoring.
The high melting point oxidation-resistant hafnium oxide (HfO2) is used as the speckle raw material, and is fully mixed with dilute nitric acid and deionized water to prepare the suspension, and is sprayed onto the surface of the SiC ceramic matrix composite sample through a spray gun. The natural process of surface oxidation of SiC ceramic matrix composite in a high-temperature aerobic environment to generate SiO2 is used to pin the speckle surface.
The prepared speckle has excellent temperature resistance and high adhesion, and is not prone to oxidation, deformation or shedding. It can be used for a long time in an air and argon atmosphere at 1500°C, ensuring the accuracy and reliability of high-temperature strain measurement of SiC ceramic matrix composites.
Smart Images

Figure CN120172758A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of speckle preparation for high-temperature strain measurement, and particularly relates to a high-temperature speckle preparation method suitable for silicon carbide ceramic matrix composites. Background Art
[0002] Due to its excellent properties of high specific strength, high specific modulus, high temperature resistance, and creep resistance, SiC ceramic matrix composites have broad application prospects as thermal structure components of aeroengines and hypersonic aircraft. In practical applications, SiC ceramic matrix composites often need to serve in a high-temperature aerobic environment of 1300 - 1500 °C. Therefore, it is of great significance to characterize the high-temperature mechanical properties of SiC ceramic matrix composites and clarify their damage and failure mechanisms. Digital Image Correlation (DIC) technology can calculate the full-field strain of materials and characterize the damage evolution process by collecting and comparing the deformed images of materials during mechanical tests. Currently, DIC has been widely used for in-situ monitoring of damage and analysis of damage and failure mechanisms of SiC ceramic matrix composites. And preparing high-quality speckles on the surface of the test specimen is the key to ensuring the DIC measurement effect. At present, a variety of high-temperature speckles suitable for SiC ceramic matrix composites have been developed, but most of the speckles can be used at temperatures below 1200 °C, and the application environment is mostly vacuum or inert atmosphere. There are few reports on speckles suitable for high-temperature aerobic environments. Developing high-temperature resistant and antioxidant speckles suitable for SiC ceramic matrix composites is the only way to realize in-situ monitoring of strain evolution in a near-service high-temperature environment, and it can provide key data support for the analysis of damage and failure mechanisms of SiC ceramic matrix composites.
[0003] In the prior art:
[0004] In Document 1 "W. Li, S. Wu, J. Zhu, W. Guan, E. Jin, H. Liu. Digital image correlation technique for full-field deformation of SOFC at 1300 °C: An efficient speckle pattern for porous and diffusible substrates. Optics and Laser in Engineering, 2025, 186, 108849.", a speckle was made by mixing a binder mainly composed of sodium silicate, cobalt oxide powder, and water in a ratio of 6.6:1:1. However, this speckle will change color at 600 - 700 °C and cannot be used above 1300 °C.
[0005] Reference 2 "Archer T, Beauchêne, Pierre, Huchette, Cédric, Hild, Global digital image correlation up to very high temperatures with grey level corrections, Measurement Science and Technology, 2020, 31" used SiC powder as the speckle and attempted DIC tests at 1860 °C. However, SiC undergoes intense oxidation around 1400 °C, causing the grey level residuals to increase. Therefore, SiC powder is not suitable as a speckle in a high-temperature aerobic environment.
[0006] In Reference 3 "Z. Pan, S. Huang, Y. Su, M. Qiao, Q. Zhang. Strain field measurements over 3000 °C using 3D-Digital image correlation. Optics and Lasers in Engineering, 2020, 127(Apr.): 105942.1 - 105942.9", tantalum carbide and alcohol were mixed in a mass ratio of 1:2, and the resulting paste-like mixture was applied to the specimen surface by dot coating as the speckle. The formed speckles had large and uneven particle sizes, making it impossible to achieve high-precision strain measurement, and tantalum carbide also undergoes oxidation in a high-temperature aerobic environment.
[0007] In Patent 1 "Mao Weiguo, Peng Zhangbao, Dai Cuiying, etc. Method for preparing speckles suitable for high-temperature environments. CN103792117A", the specimen was placed in a prepared iron hydroxide colloid, and the iron hydroxide colloid was decomposed by heating, and the generated iron oxide was deposited on the specimen surface to form speckles. However, this process is relatively cumbersome and it is difficult to control the size of the generated speckles. In addition, the speckles cannot be used at temperatures above 1566 °C (the melting point of iron oxide).
[0008] In Patent 2 "Meng Songhe, Wang Boyi, Xu Chenghai, etc. A method and device for preparing high-temperature speckles. CN118129630A", first, the speckle liquid was printed on the specimen surface by 3D printing, and then it was placed in a hot press furnace, maintaining a vacuum of 10 -2 -10 -3After Pa, the pressure and temperature are successively increased to a constant value at a certain constant rate and then maintained for a period of time, and finally cooled to normal temperature and pressure to obtain high-temperature resistant speckles. This kind of speckle preparation process is complex and requires high experimental equipment, making it difficult to achieve low-cost and large-scale promotion. At the same time, the highest operating temperature of the prepared speckles is 1400 °C, which cannot meet the strain measurement requirements at higher temperatures.
[0009] Patent 3 "Pan Bing, Wu Dafang. A method for making speckles for deformation measurement in high-temperature environment. CN101905210A" prepares high-temperature speckles by mixing high-temperature inorganic glue and alcohol in a volume ratio of 7:3 and then adding 10 wt% of CoO powder. However, the high-temperature glue is expensive and cannot be used above 1200 °C.
[0010] In summary, the following defects still exist in the prior art:
[0011] 1) SiC ceramic matrix composites often need to be used at service temperatures of 1300 - 1500 °C or even higher. The temperature resistance of the speckles is insufficient, and the high-temperature adhesion is insufficient.
[0012] 2) The current high-temperature speckle system has problems such as oxidation, deformation, and easy shedding in a high-temperature aerobic environment, and cannot perform strain measurement and damage monitoring on SiC ceramic matrix composites in a high-temperature aerobic environment.
[0013] 3) The equipment requirements for preparing high-temperature speckles are high, the cost is expensive, the steps are cumbersome, and the preparation cycle is long, which restricts the popularization and application of high-temperature speckles.
[0014] In order to better monitor the strain evolution process of SiC ceramic matrix composites and support their engineering applications, it is urgent to develop a high-temperature resistant and antioxidant speckle preparation process, so that the prepared speckles can be used reliably in a high-temperature aerobic environment, with low equipment dependence, low cost, and easy to achieve large-scale promotion. Summary of the Invention
[0015] The technical problem to be solved by the present invention is:
[0016] A method for preparing high-temperature speckles suitable for SiC ceramic matrix composites.
[0017] Using hafnium oxide (HfO2) with high melting point and antioxidant as the speckle raw material, fully mixing it with dilute nitric acid and deionized water to prepare a suspension, and spraying the suspension onto the surface of the SiC ceramic matrix composite specimen by a spray gun;
[0018] Furthermore, by utilizing the natural process of the surface oxidation of SiC ceramic matrix composites to generate SiO2 in a high-temperature aerobic environment, the prepared speckles are pinned on the specimen surface.
[0019] The speckles prepared by this method have excellent temperature resistance and high adhesion, and are not prone to oxidation, deformation or shedding. After experimental verification, the speckles still adhere firmly to the surface of the SiC ceramic matrix composite specimen after heat treatment in an air and argon atmosphere at 1500 °C for 2 h, and no deformation or shedding occurs during mechanical tests (uniaxial tension, three-point bending). Accurate strain measurement results are obtained by combining the DIC technique.
[0020] To achieve the above object, the present invention adopts the following technical solutions:
[0021] A method for preparing high-temperature speckles applicable to SiC ceramic matrix composites, comprising the following preparation steps:
[0022] S1 Weigh 0.1 - 5 g of metal oxide powder, 0.05 - 0.5 g of a stabilizer solution with a mass fraction of 1 - 5% and 5 g of water;
[0023] S2 Magnetically stir the above system at 25 °C for 2 - 48 h;
[0024] S3 Spray the speckle liquid obtained in step (2) onto the surface of the SiC ceramic matrix composite using a spray gun and dry it;
[0025] S4 Conduct mechanical tests.
[0026] As a further preferred method, in S4,
[0027] If the mechanical test is carried out in an air atmosphere, the specimen obtained in step (3) can be directly used for the experiment.
[0028] As a further preferred method, in S4,
[0029] If the experiment is carried out in a vacuum or inert atmosphere, the specimen obtained in step (3) needs to be pre-oxidized, and then the mechanical properties are tested.
[0030] As a further preferred method, in S4,
[0031] If the experiment is carried out in a vacuum or inert atmosphere, the conditions for pre-oxidation are: pre-oxidation in an air atmosphere at 600 - 1500 °C for 0.25 - 3 h.
[0032] As a further preferred method, in S1, the metal oxide powder is any one or more of HfO2 powder, Al2O3 powder, ZrO2 powder, and TiO2 powder.
[0033] As a further preferred method, in S1, the stabilizer solution is: 0.05 - 0.5 g of a dilute nitric acid solution or aluminum dihydrogen phosphate solution or sodium silicate solution with a mass fraction of 1 - 5%.
[0034] As a further preferred embodiment, in S1, the water is deionized water.
[0035] As a further preferred embodiment, in S3, the drying conditions are: an air atmosphere at 100 - 200 °C, and the drying time is 1 - 3 h.
[0036] Compared with the prior art, the design of the present invention is reasonable and has the following beneficial effects:
[0037] 1) In the present invention, HfO₂, dilute nitric acid, and deionized water in the speckle liquid act synergistically as raw materials, and a high-temperature speckle suitable for SiC ceramic matrix composites is prepared by spraying onto the surface of the specimen with a spray gun. The prepared speckles have a small particle size (10 - 30 μm) and are evenly distributed;
[0038] 2) The speckles prepared by this method have good adhesiveness at 1500 °C for a long time, and can be applied in a high-temperature aerobic environment, a high-temperature vacuum / inert gas atmosphere environment. The speckles have strong applicability and high reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a photo of the speckles prepared in Example 1 of the present invention. Figure a is the photo before heat treatment, and Figure b is the photo after tensile fracture at 25 °C after heat treatment in an air atmosphere at 1500 °C for 2 h.
[0040] Figure 2 It is a photo of the speckles prepared in Example 2 of the present invention. Figure a is the photo before heat treatment, Figure b is the photo after heat treatment in an argon atmosphere at 1500 °C for 2 h after pre-oxidation at 1500 °C for 0.25 h, and Figure c is the photo after tensile fracture at 25 °C.
[0041] Figure 3 It is a photo of the speckles prepared in Example 3 of the present invention. Figure a is the photo after drying in an air atmosphere at 100 °C for 3 h, and Figure b is the photo after tensile fracture in a high-temperature air atmosphere.
[0042] Figure 4 It is a photo of the speckles prepared in Comparative Example 1 of the present invention. Figure a is the photo before heat treatment, and Figure b is the photo after heat treatment in an argon atmosphere at 1500 °C for 2 h.
[0043] Figure 5 It is a photo of the speckles prepared in Comparative Example 2 of the present invention. Figure a is the photo before heat treatment, and Figure b is the photo after heat treatment in an argon atmosphere at 1500 °C for 2 h.
[0044] Figure 6 It is a photo of the speckles prepared in Comparative Example 3 of the present invention. Figure a is the photo before heat treatment, and Figure b is the photo after heat treatment in an argon atmosphere at 1500 °C for 2 h.
[0045] Figure 7It is the speckle photograph prepared in Comparative Example 4 of the present invention. Figure a is the photograph before heat treatment, and Figure b is the photograph after heat treatment at 1500 °C for 2 h in an argon atmosphere.
[0046] Figure 8 It is the scanning electron microscope photograph of the speckles prepared in Example 1 of the present invention after heat treatment in an air atmosphere at 1500 °C. The white spherical substance in the middle is the prepared speckles.
[0047] Figure 9 It is the energy dispersive spectrometer (EDS) analysis result of the speckles prepared in Example 1 of the present invention after heat treatment in an air atmosphere at 1500 °C. Among them, Figure a is the distribution map of oxygen element, Figure b is the distribution map of hafnium element, and Figure c is the distribution map of silicon element.
[0048] Figure 10 It is the scanning electron microscope picture of silicon dioxide formed on the surface of the composite material sample with speckles prepared in Example 2 of the present invention after pre-oxidation and heat treatment at 1500 °C for 2 h in an argon atmosphere.
[0049] Figure 11 It is the EDS analysis result of silicon dioxide formed on the surface of the composite material sample with speckles prepared in Example 2 of the present invention after pre-oxidation and heat treatment at 1500 °C for 2 h in an argon atmosphere. Among them, Figure a is the distribution map of oxygen element, and Figure b is the distribution map of silicon element.
[0050] Figure 12 It is the strain nephogram and the photograph after tensile fracture of the sample after heat treatment in an air atmosphere in Example 1 of the present invention when approaching fracture at 25 °C.
[0051] Figure 13 It is the strain nephogram and the photograph after tensile fracture of the sample after heat treatment in an argon atmosphere in Example 2 of the present invention when approaching fracture at 25 °C.
[0052] Figure 14 It is the strain nephogram and the photograph after tensile fracture obtained when the sample in Example 3 of the present invention is stretched in a high-temperature air atmosphere. Figure a is the photograph after the sample is tensile fractured, Figure b is the strain nephogram when the sample is about to appear cracks, and Figure c is the strain nephogram when cracks appear on the surface of the sample. Detailed implementation manners
[0053] In order to make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described below in conjunction with embodiments:
[0054] Example 1
[0055] (1) Weigh 0.1 - 5 g of HfO2 powder, 0.05 - 0.5 g of dilute nitric acid solution with a mass fraction of 1 - 5%, and 5 g of deionized water;
[0056] (2) Stir the above system magnetically at 25 °C for 2 - 48 h;
[0057] (3) Spray the speckle liquid obtained in (2) onto the surface of the SiC ceramic matrix composite using a spray gun, and dry it in an oven at 100 - 200 °C in an air atmosphere for 1 - 3 h. The function is to prevent the rapid evaporation of water during the heating process in step (4), which may affect the adhesion of the speckles;
[0058] (4) Heat-treat at 1500 °C for 2 h in an air atmosphere ( Figure 1 、 Figure 8 、 Figure 9 );
[0059] (5) Conduct mechanical tests at 25 °C and observe using DIC ( Figure 12 ).
[0060] Figure 1 is the speckle photograph prepared in Example 1 of the present invention. Figure a is the photograph before heat treatment, and Figure b is the photograph after tensile fracture at 25 °C after heat treatment in an air atmosphere at 1500 °C for 2 h. It can be observed that the speckles still adhere to the surface of the specimen after heat treatment and do not fall off. The part in the dotted circle is caused by gold spraying after treatment, rather than a change in the nature of the speckles.
[0061] Figure 8 is the scanning electron microscope photograph of the speckles prepared in Example 1 of the present invention after heat treatment in an air atmosphere at 1500 °C. The white spherical substance in the middle is the prepared speckles.
[0062] Figure 12 is the strain nephogram and the photograph after tensile fracture of the specimen after heat treatment in an air atmosphere at 25 °C in Example 1 of the present invention when approaching fracture. It can be seen from the figure that the strain concentration position of the specimen corresponds to the crack position, which proves the accuracy of strain calculation and verifies the reliability of the speckles.
[0063] From Figure 1 、 Figure 8 and Figure 9 it can be seen that the speckles adhere well after heat treatment in an air atmosphere at 1500 °C for 2 h and do not fall off. The speckle particles are small and evenly distributed, which is very suitable for DIC observation. From Figure 12 it can be seen that the strain concentration position coincides with the crack position, which proves the accuracy of strain calculation and verifies the reliability of the prepared speckles.
[0064] Example 2
[0065] (1) Weigh 0.1 - 5 g of HfO2 powder, 0.05 - 0.5 g of dilute nitric acid solution with a mass fraction of 1 - 5%, and 5 g of deionized water;
[0066] (2) Stir the above system magnetically at 25 °C for 2 - 48 h;
[0067] (3) Spray the speckle liquid obtained in (2) onto the surface of the SiC ceramic matrix composite using a spray gun, and dry it in an oven at 100 - 200 °C in an air atmosphere for 1 - 3 h. The function is to prevent the rapid evaporation of water during the heating process in step (4), which may affect the adhesion of the speckles;
[0068] (4) Pre - oxidize the specimen in an air atmosphere at 600 - 1500 °C for 0.25 - 3 h so that the speckles can be firmly pinned on the surface of the specimen, and then heat - treat it in an argon atmosphere at 1500 °C for 2 h ( Figure 2 、 Figure 10 、 Figure 11 )
[0069] (5) Conduct mechanical tests at 25 °C and observe using DIC ( Figure 13 ).
[0070] Figure 2 is the speckle photograph prepared in Example 2 of the present invention. Figure a is the photograph before heat - treatment, Figure b is the photograph after heat - treatment at 1500 °C in an argon atmosphere for 2 h after pre - oxidation at 1500 °C for 0.25 h, and Figure c is the photograph after tensile fracture at 25 °C. It can be observed that the speckles still adhere to the surface of the specimen after heat - treatment and do not fall off.
[0071] Figure 10 is the scanning electron microscope image of the silicon dioxide formed on the surface of the composite material specimen with speckles prepared in Example 2 of the present invention after pre - oxidation and heat - treatment in an argon atmosphere at 1500 °C for 2 h.
[0072] Figure 11 is the EDS analysis result of the silicon dioxide formed on the surface of the composite material specimen with speckles prepared in Example 2 of the present invention after pre - oxidation and heat - treatment in an argon atmosphere at 1500 °C for 2 h. Among them, Figure a is the distribution map of oxygen element, and Figure b is the distribution map of silicon element. It can be seen from the figure that the oxidation of the SiC matrix generates SiO2 on the surface of the composite material specimen and pins the prepared speckles.
[0073] Figure 13 is the strain nephogram and the photograph after tensile fracture of the specimen after heat - treatment in an argon atmosphere at 25 °C in Example 2 of the present invention when the tensile is close to fracture. It can be seen from the figure that the strain concentration position of the specimen corresponds to the crack position, which proves the accuracy of the strain calculation and verifies the reliability of the speckles.
[0074] As Figure 2 can be seen, the speckles adhere well after heat - treatment in an argon atmosphere at 1500 °C for 2 h and do not fall off. The speckle particles are small and evenly distributed, which is very suitable for DIC observation. AsFigure 13 It can be seen that the strain concentration position coincides with the crack position, which proves the accuracy of the strain calculation and verifies the reliability of the prepared speckles.
[0075] Example 3
[0076] (1) Weigh 0.1 - 5 g of HfO₂ powder, 0.05 - 0.5 g of dilute nitric acid solution with a mass fraction of 1 - 5%, and 5 g of deionized water;
[0077] (2) Magnetically stir the above system at 25 °C for 2 - 48 h;
[0078] (3) Spray the speckle liquid obtained in (2) onto the surface of the SiC ceramic matrix composite using a spray gun, and dry it in an oven at 100 - 200 °C in an air atmosphere for 1 - 3 h. The function is to prevent the rapid evaporation of water during the heating process in step (4), which may affect the adhesion of the speckles. Figure 3 )
[0079] (4) Conduct mechanical tests in a high-temperature air atmosphere at 1100 - 1200 °C and observe using DIC. Figure 14 )
[0080] (Compared with Example 1: 1. There is no heat treatment in an air atmosphere at 1500 °C; 2. During the mechanical test, it is in a high-temperature air atmosphere at 1100 - 1200 °C (in Example 1, it is at 25 °C).)
[0081] Figure 3 This is the speckle photograph prepared in Example 3 of the present invention. Figure a is the photograph after drying in an air atmosphere at 100 °C for 3 h, and Figure b is the photograph after tensile fracture in a high-temperature air atmosphere. It can be observed that the speckles still adhere to the surface of the specimen after tensile fracture in a high-temperature air atmosphere and do not fall off.
[0082] Figure 14 This is the strain nephogram and the photograph after tensile fracture of the specimen during tensile in a high-temperature air atmosphere in Example 3 of the present invention. Figure a is the photograph after the specimen is tensile fractured, Figure b is the strain nephogram when the crack is about to appear on the specimen, and Figure c is the strain nephogram when the crack appears on the surface of the specimen. The blank at the position with the maximum strain in Figure c indicates that macroscopic damage has occurred to the specimen, and the specimen matrix together with the surface speckles has fallen off, rather than the insufficient adhesion of the speckles themselves. It can be seen from the figure that the strain concentration position of the specimen corresponds to the crack position, which proves the accuracy of the strain calculation and verifies the reliability of the speckles.
[0083] From Figure 3 it can be seen that after the specimen is tensile fractured in a high-temperature air atmosphere, the speckles still adhere well and do not fall off. From Figure 14 it can be seen that the strain concentration position coincides with the crack position, which proves the accuracy of the strain calculation and verifies the reliability of the prepared speckles in a high-temperature aerobic environment.
[0084] Comparative Example 1
[0085] (1) Weigh 0.1 - 5 g of HfO₂ powder, 0.05 - 0.5 g of dilute nitric acid solution with a mass fraction of 1 - 5%, and 5 g of deionized water;
[0086] (2) Magnetically stir the above system at 25 °C for 2 - 48 h;
[0087] (3) Spray the speckle liquid obtained in (2) onto the surface of the SiC bulk ceramic using a spray gun, and dry it in an oven at 100 - 200 °C in an air atmosphere for 1 - 3 h. The function is to prevent the rapid evaporation of water during the heating process in step (4) from affecting the adhesion of the speckles;
[0088] (4) Heat-treat in an argon atmosphere at 1500 °C for 2 h ( Figure 4 ).
[0089] Figure 4 It is the speckle photograph prepared in Comparative Example 1 of the present invention. Figure a is the photograph before heat treatment, and Figure b is the photograph after heat treatment at 1500 °C in an argon atmosphere for 2 h. It can be observed that part of the speckles has fallen off, and the substrate of the speckles is the SiC bulk ceramic.
[0090] From Figure 4 it can be seen that part of the speckles has fallen off after heat treatment in an argon atmosphere at 1500 °C for 2 h. Therefore, it is necessary to perform pre-oxidation treatment to improve the adhesion of the speckles in a high-temperature inert / vacuum atmosphere.
[0091] (Compared with Example 1: Heat treatment in an argon atmosphere at 1500 °C for 2 h (in Example 1, it is heat treatment at 1500 °C in an air atmosphere))
[0092] Comparative Example 2
[0093] (1) Weigh 0.1 - 5 g of HfO₂ powder, 0.05 - 0.5 g of high-temperature glue, and 5 g of deionized water;
[0094] (2) Mix the above system thoroughly at 25 °C;
[0095] (3) Since the viscosity of the high-temperature glue will clog the spray gun, the speckle liquid is brushed onto the surface of the SiC bulk ceramic with a brush, and dried in an oven at 100 - 200 °C in an air atmosphere for 1 - 3 h. The function is to prevent the rapid evaporation of water during the heating process in step (4) from affecting the adhesion of the speckles;
[0096] (4) Heat-treat in an argon atmosphere at 1500 °C for 2 h ( Figure 5 ).
[0097] Figure 5It is the speckle photograph prepared in Comparative Example 2 of the present invention. Figure a is the photograph before heat treatment, and Figure b is the photograph after heat treatment at 1500 °C for 2 h in an argon atmosphere. It can be observed that a large number of speckles have fallen off, and the substrate of the speckles is SiC bulk ceramic.
[0098] It can be seen from Figure 5 that a large number of speckles have fallen off after heat treatment at 1500 °C in an argon atmosphere for 2 h. Therefore, using high-temperature glue cannot meet the high-precision full-field strain measurement of SiC ceramic matrix composites at 1500 °C.
[0099] Comparative Example 3
[0100] (1) Weigh 0.1 - 5 g of Al2O3 powder, 0.05 - 0.5 g of dilute nitric acid solution with a mass fraction of 1 - 5% and 5 g of deionized water;
[0101] (2) Mix the above system thoroughly at 25 °C;
[0102] (3) Spray the speckle liquid obtained in (2) onto the surface of the SiC bulk ceramic using a spray gun, and dry it in an oven at 100 - 200 °C in an air atmosphere for 1 - 3 h. The role is to prevent the rapid evaporation of water during the heating process in step (4) from affecting the adhesion of the speckles due to too fast heating rate;
[0103] (4) Heat-treat for 2 h in an argon atmosphere at 1500 °C ( Figure 6 ).
[0104] Figure 6 It is the speckle photograph prepared in Comparative Example 3 of the present invention. Figure a is the photograph before heat treatment, and Figure b is the photograph after heat treatment at 1500 °C for 2 h in an argon atmosphere. It can be observed that a large number of speckles have fallen off, and the substrate of the speckles is SiC bulk ceramic.
[0105] It can be seen from Figure 6 that a large number of speckles have fallen off after heat treatment at 1500 °C in an argon atmosphere for 2 h. Comparing with Comparative Example 1, it can be known that using HfO2 powder as the speckle has a better adhesion effect and is more suitable as the high-temperature speckle of SiC ceramic matrix composites.
[0106] Comparative Example 4
[0107] (1) Weigh 0.1 - 5 g of HfO2 powder, 0.05 - 0.5 g of aluminum dihydrogen phosphate solution with a mass fraction of 1 - 5% and 5 g of deionized water;
[0108] (2) Mix the above system thoroughly at 25 °C;
[0109] (3) Spray the speckle liquid obtained in (2) onto the surface of the SiC ceramic matrix composite material using a spray gun, and dry it in an oven at 100 - 200 °C in an air atmosphere for 1 - 3 h. The function is to prevent the rapid evaporation of moisture during the heating process in step (4), which may affect the adhesion of the speckles;
[0110] (4) Heat-treat in an argon atmosphere at 1500 °C for 2 h ( Figure 7 ).
[0111] Figure 7 This is the speckle photograph prepared in Comparative Example 4 of the present invention. Figure a is the photograph before heat treatment, and Figure b is the photograph after heat treatment in an argon atmosphere at 1500 °C for 2 h. It can be observed that a large number of speckles have fallen off.
[0112] It can be seen from Figure 7 that a large number of speckles have fallen off after heat treatment in an argon atmosphere at 1500 °C for 2 h. Therefore, using an aluminum dihydrogen phosphate solution as a stabilizer for HfO2 powder cannot meet the high-precision full-field strain measurement of SiC ceramic matrix composites at 1500 °C.
[0113] The above is only the preferred embodiment of the present invention, and it does not limit the patent scope of the present invention. Any equivalent transformation made using the present invention is within the patent protection scope of the present invention.
Claims
1. A method for preparing high temperature speckle for silicon carbide ceramic matrix composite materials, characterized in that: The method comprises the following preparation steps: S1 weigh 0.1-5g of metal oxide powder, 0.05-0.5g of 1-5% stabilizer solution and 5g of water; S2. The above system is magnetically stirred at 25°C for 2-48h; S3: spraying the speckle liquid obtained in step (2) onto the surface of the SiC ceramic matrix composite material using a spray gun, and drying; S4 was subjected to mechanical testing.
2. The method for preparing high temperature speckle suitable for silicon carbide ceramic matrix composite materials according to claim 1, characterized in that: In S4, If the mechanical test is carried out in an air atmosphere, the sample obtained in step (3) can be directly used for the experiment.
3. The method for preparing high temperature speckle suitable for silicon carbide ceramic matrix composite materials according to claim 1, characterized in that: In S4, If the experiment is conducted in a vacuum or inert atmosphere, the sample obtained in step (3) needs to be pre-oxidized before being tested for mechanical properties.
4. The method for preparing high temperature speckle suitable for silicon carbide ceramic matrix composite materials according to claim 3, characterized in that: In S4, If the experiment is carried out in a vacuum or inert atmosphere, the pre-oxidation conditions are: pre-oxidation in an air atmosphere at 600-1500°C for 0.25-3h.
5. The method for preparing high temperature speckle suitable for silicon carbide ceramic matrix composite materials according to claim 1, characterized in that: In S1, the metal oxide powder is any one or more of HfO2 powder, Al2O3 powder, ZrO2 powder, and TiO2 powder.
6. The method for preparing high temperature speckle suitable for silicon carbide ceramic matrix composite materials according to claim 1, characterized in that: In S1, the stabilizer solution is: 0.05-0.5g of dilute nitric acid solution or aluminum dihydrogen phosphate solution or sodium silicate solution with a mass fraction of 1-5%.
7. The method for preparing high temperature speckle suitable for silicon carbide ceramic matrix composite materials according to claim 1, characterized in that: In S1, water is deionized water.
8. The method for preparing high temperature speckle suitable for silicon carbide ceramic matrix composite materials according to claim 1, characterized in that: In S3, the drying conditions are: 100-200°C air atmosphere, and the drying time is 1-3h.
Citation Information
Patent Citations
Speckle making method for deformation measurement in high temperature environment
CN101905210A
Method for preparing speckles suitable for high-temperature environment
CN103792117A
Cited By
Preparation method and application of high-temperature-resistant high-Mach gas impact speckle applicable to silicon carbide-based composite material
CN121315835A